Generation Expansion Planning: A Bibliometric Review - W. Sunanda (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2026)
Generation expansion planning is a prominent topic of energy-related scientific discourse. Due to operational constraints, the penetration of renewable energy sources, and uncertainty, there have been numerous changes in the planning of generation expansion. This article provides a bibliometric analysis of recent research on generational expansion planning. Relevant authors, sources, terms, disciplines, and conceptual analysis are used for bibliometric analysis. This bibliometric is based on a Scopus database data set for the years 2013 to 2023.